Comparative evaluation of various substrates for cost-effective mass multiplication of Beauveria bassiana - Puneet, K; Meena, R S; Raju, S V S; Singh, S P; Vinita, S; Giri, G S (Plant Science Today, 2026)
The white muscardine fungus, Beauveria bassiana (Bals.-Criv.) Vuill., with wide biocontrol potential, requires cost-effective mass multiplication methods to enhance adoption at the field level. A study was conducted at Biocontrol Laboratory, Department of Entomology and Agricultural Zoology, Institute of Agricultural Sciences, Banaras Hindu University, Varanasi, for a comparative evaluation of grain-based and artificial substrates for its mass multiplication. Among 6 grains tested, sorghum, chickpea, wheat, rice, maize and green gram; sorghum showed the highest spore yield of 90.96 × 10⁷ spores g-1 and a peak growth rate increase of 138.68 % between days 14 and 21. It also exhibited as the most cost effective substrate, producing 2860.35 × 10⁷ spores ₹-1, surpassing chickpea (60.12 × 10⁷ spores g-1) and wheat (33.08 × 10⁷ spores g-1). Maize and green gram performed poorly in biological and economic terms. Among artificial media, PDA (Potato Dextrose Agar) was the most effective, showing the highest mean radial growth of 36.83 mm and sporulation of 52.54 × 107 spores mL-1, yielding 24,783.02 × 107 spores ₹-1. P1DA (Papaya peels Dextrose Agar) also performed well with radial growth of 31.00 mm, sporulation of 35.41 × 107 spores mL-1 and economical yield of 21,862.96 × 107 spores ₹-1, nearly twice that of BDA (Banana Dextrose Agar) which produced 18.5 × 107 spores mL-1 and 11,419.75 × 107 spores ₹-1. Thus, while PDA is biologically superior, P1DA offers a promising, cost-effective alternative for fungal propagation. This evaluation confirms sorghum and PDA as the best substrates for field- and lab-scale production, respectively.